Burn injuries in Zimbabwe: development of guidelines for physiotherapy rehabilitation of musculoskeletal impairments and functional limitations - Mudawarima, Tapfuma (Department of Health and Rehabilitation Sciences, 2022)
Background and need: Burn injuries are a major cause of hospital admission in low-income countries such as Zimbabwe and often lead to secondary complications such as disfigurements, contractures, and scar formations. The study aimed to establish “Guidelines for Rehabilitation of Musculoskeletal Impairments and Functional Limitations for Zimbabwe for Patients with Burns” based on the best evidence available. There were three good candidates for use as the source guideline, but ultimately, the Agency for Clinical Innovation (ACI) of New South Wales in Australia guidelines1 was chosen. The contextualisation of these guidelines for the Zimbabwean situation was informed by the outcomes of five sub-studies. A summary of the methodologies applied and the key results follow. Methods and Results: The Epidemiology of Burns in Zimbabwe: The characteristics of patients with burns in Zimbabwe was established through a retrospective record review (descriptive review) to characterise patients admitted with burns to the two central hospitals in Harare over fifteen months. The sample consisted of 926 admission records and 435 full patient folders were retrieved and analysed. Unfortunately, 425 full folders of children were missing and 85 folders of adults. There was a clear difference in presentation between children and adults, with children constituting over threequarters of all admissions, but with less severe injuries. Post-discharge follow-up: Access to rehabilitation and impact on Health-Related Quality of Life (HRQoL): The second study investigated the utilisation of post-discharge care, regarding referral after discharge and home programme. This was a study with a small sample, 14 adult and 23 child respondents. Despite referrals having been made to local rehabilitation departments, there was practically no further post-discharge contact with rehabilitation and only a single person received post-discharge rehabilitation. Both Health-Related Quality of Life (HRQoL) instruments used by the adult respondents indicated less impact on physical domains of functioning with the greatest impact in pain and emotional well-being. In the absence of trained counsellors, rehabilitation therapists might need to step into this role. Systematic review: The broad objective of this review was to systematically evaluate the effectiveness, safety and applicability to low-income countries of therapeutic exercises utilised by physiotherapists to improve function in patients with burns. The review, which included 19 papers, established that exercises (either resistance or aerobic), are effective and generally have a positive effect on muscle strength and aerobic capacity. However, there was a risk of bias in many of the papers and the evidence is not of high quality. As most of the research enrolled paediatric patients older than seven years and no adverse effects were reported, it can be concluded that resistance exercise is safe for this group of patients. However, as most children admitted with burns are younger than seven years, exercise needs to be carefully monitored in this group as safety and efficacy have not been proven for younger children. The results from this support the use of aerobic and resistance as an important component of a burn rehabilitation program as they have shown to improve muscle strength aerobic capacity and functional status even after hospital discharge, especially in patients with severe burns. Documentation of the current rehabilitation practice: This phase documented clinical interventions used to treat musculoskeletal problems by observation of seven rehabilitation workers (not only physiotherapists), based in the five central hospitals, one provincial and one district hospital. The treatments of five adults and five paediatric patients were observed at each hospital, a total of 70 treatments in all. The most significant finding was that the management of patients with burns was offered by a single rehabilitation worker a Physiotherapists (PT), Occupational Therapists (OT) or Rehabilitation Technician (RT), working in Burns' Units without any specialised training or additional courses. The management of burns across all hospitals was similar, and information saturation was reached with the planned number of observations. Passive and active movements were used almost universally, and the patients received a ward programme, which included positioning. Sitting and standing were included in some patients and patients were monitored for any adverse effects. A major weakness observed was the lack of baseline assessment or treatment progress during treatment. No compression bandages were applied and no scar tissue massage was done. Identification and adaptation of the suitable guidelines: Following a literature search and examination of different guidelines by two independent reviewers, the Agency for Clinical Innovation of New South Wales, Australia1 was chosen as a candidate for amendment. The guidelines were amended based on the results of the previous studies and subjected to a Delphi process with four to six Zimbabwean rehabilitation therapists who were experienced in the field of burn management. A credible set of guidelines for Zimbabwe for the rehabilitation of musculoskeletal impairments and functional limitations was thus produced. Conclusion: The current study adds to the body of knowledge through the development of guidelines for the physiotherapy rehabilitation of musculoskeletal impairments and functional limitations for patients with burns in low- and middle-income countries. The thesis has provided an evidence-based framework for patients, rehabilitation workers and policymakers to inform the provision of effective management of patients with burns. The Zimbabwe Guidelines should be regarded as a first attempt rather than the final version and hopefully will be subjected to further review as they are tried out in practice.